Evaluación del bienestar animal de ganado bovino y su influencia en los sistemas productivos de carne en fincas del cantón Bolívar - Alcívar Mendoza, Xiomara Monserrat (2024)
The present research work aimed to evaluate the animal welfare of cattle and its influence on the meat production systems in 12 farms of the Bolívar canton located in the province of Manabí; collecting information through interviews about cattle breeds, different management environments of the production systems, slaughtering techniques; in addition, texture profile characterization analyses and physicochemical analyses were performed. There are 4 types of Holsteins breed cattle, 11 mestizo and one Brahma, 100% of the interviewed producers state that the applied production system is the traditional one, most grass-fed, and for slaughtering purposes if it has completed its dairy cycle regardless of the breed. The meat from the farms studied reported the following results: 5.87 to 6.33 pH, 0.10 to 0.15% acidity, indicating that only the pH is within the range established by the NTE INEN 2346 standard; 10 to 60 CRA, 25 to 116 N of hardness, -0.023 to 0.075 J of adhesiveness, cohesion from 0 to 0.51N/mm2, -2.72 to -0.35 N of adhesive strength, Gumminess from 0 to 60N, elasticity between 0 and 0.76Pa, and finally the chewiness ranging from 0 to 36.53N. These findings demonstrate the importance of evaluating the incidence of animal welfare of cattle in the meat production to guarantee its quality and compliance with established standards, results that are useful for the meat industry and consumers in general.